MEN’S SEXUAL TRAUMA RESISTANCE IN BLACK AMERICAN FOLKLORE: A POSTCOLONIAL CRITICISM OF NEGRO “WOMAN TALES” - Ntamwana, Simon (International Journal of Humanity Studies (IJHS), 2023)
The purpose of this paper “Men’s Sexual Trauma Resistance in Black American Folklore: A Postcolonial Criticism of Negro “Woman Tales” from the Gulf States” was to discuss the reflection of postcolonial sexual trauma and resistance to it through storytelling among African Americans in the Gulf States. The study was concerned with 3 folktales classified under the cycle “Woman Tales”. The folktales were selected from the collection made by Zora Neale Hurston in the southern states of Alabama, Florida, and Louisiana from 1927 to 1930 and compiled in the book Every Tongue Got to confess: Negro Folktales from the Gulf States (2001). The postcolonial approach and trauma theory based on the interpretative qualitative method and library research was used in the discussion of the selected folktales. It was found that the performance of the “Woman Tales” is informed by the black men’s traumatic memories of slavery and post-slavery emasculation. Black male narrators imitate trauma narratives in which they reflect male sexual trauma and recreate black woman identity to contain it. Through this imitation and reflection, the folktales challenge the legacy of the plantation patriarchy by reconstructing a woman's identity that is docile to black masculinity.